ANALISIS PENGARUH KEPUASAN KOMPENSASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (Studi Pada Kantor Pusat Bank Jateng Semarang) - Suprana, Riski; Ratnawati, Intan (Diponegoro Journal of Management, 2012)
Performance is an overview of the level of achievement of the implementation of an action or policy in achieving the goals, objectives, vision and mission of the organization. In the achievement of corporate goals is usually the company experienced a high turnover rate, with a high turnover rate can affect the performance of the organization and lead to ineffective organizations. One step is to prevent the release of employee compensation that is intended to provide a sense of satisfaction will be compensation given by the organization to realize the goals, vision and mission. Research conducted at the headquarters of the Bank of Central Java is intended to analyze the effect of variable compensation satisfaction and organizational commitment on employee performance. The research was conducted at the Bank's headquarters in Semarang in Central Java. The number of samples is set as 96 respondents using judgment samples and methods of data analysis is the analysis of path (jalur) with the help of SPSS progran. The results of the testing of the hypothesis, suggesting that the variable compensation satisfaction and organizational commitment have a positive impact on employee performance. The variable that has the most impact is organizational commitment. The implications of this study are compensated satisfaction and organizational commitment have an equally important role, both individually and together in improving employee performance. Â